EFFECT OF USING FERMENTATION PALM KERNEL CAKE Morinda Citrifolia EXTRACT IN Broiler RATION ON CARCASS PERCENTAGE, PERCENTAGE FAT ABDOMINAL, MARBLING, AND COOKING LOSS - Valentinus Peternakan (Jurnal Sains Peternakan, 2015)
The aim of this research was to know the effect of using fermentation palm kernel cake and morinda citrifolia extract in broiler ration on carcas percentage, fat abdominal, marbling, and cooking loss.Material used were 96 unsex broiler (DOC), strain MB-202P production PT. Japfa Comfeed Indonesia Tbk. Method used was experiment. The tratment arranged with completly random design eight treatment 4 x 2 factorial. Each experimental unit consist of four broiler. The treatment were P0M0= 0% fermented prduct no morinda citrifolia, P1M0= 10% fermented product no morinda citrifolia, P2M= 20% fermented product no morinda citrifolia, P3= 30% fermented product no morinda citrifolia, P0M1= 0% fermented product with morinda citrifolia extract, P1M1= 10% fermented product with morinda citrifolia, P2M1= 20% fermented product with morinda citrifolia, P3M1= 30% fermented product with morinda citrifolia. Result of this search shown that there was no significant on carcass percentage (P>0.05), and no significant on marbling (P>0.05). While very significant on percentage fat abdominal (P<0.01) and very significant on cooking loss (P<0.01). Average of significant on percentage fat abdominal were (42,82%), (41,68%), (40,28%), (38,20%), (35,35%), (33,31%), (32,60%) and very significant on cooking loss were (49,96%), (48,90%), and (53,03%). It could be concluded that is no significant effect of using fermented palm kernel cake and morinda citrifolia extract in broiler ration on carcass percentage and marbling, while very significant on percentage fat abdominal and cooking loss. It is suggested to incerese level fermented palm cernel cake and morrinda citrifollia extract in broiler.Keyword: Fermentation, Palm Cernel Cake, Heaps, Morinda Citrifolia, Feeding, and Broiler